Metronidazole Appears Not to Be a Human Teratogen: Review of Literature - Barbara J. Struthers (Hindawi Limited, 1997)
Metronidazole is used to treat trichomoniasis, bacterial vaginosis, and other diseases. As is the case with many drugs, physicians often hesitate to use it during pregnancy, particularly in the first trimester. A review of the nearly four decades' worth of published literature on metronidazole use in pregnant women indicates that it is not teratogenic, regardless of the trimester in which it is used. On the other hand, a number of published studies indicate that bacterial vaginosis and trichomoniasis are associated with preterm birth and low birth weight. Treatment of these conditions with metronidazole during pregnancy may decrease the incidence of preterm birth and low birth weight, thus potentially decreasing the complications that can result from prematurity.